Linguistic Behaviours in Adults who Clutter and Adults who Stutter When Reading and Speaking. (30th June 2015) - Bretherton-Furness, Jess; Ward, David
Abstract: The breadth of behaviours that may be considered as cluttering continues to be contentious. The current lowest common denominator (LCD) definition of cluttering excludes the possibility of high level language deficits. However, recent studies suggest that those who clutter may have linguistic deficits alongside motor control difficulties. This paper reports behavioural findings from a larger data set collected during functional MRI scans with adults who clutter (AWC), adults who stutter (AWS) and controls (CTLs). Participants were asked to read short passages aloud and describe pictures. Speech data were analysed and coded for stuttering like dysfluencies (e.g. blocks) and normal dysfluencies (e.g. revisions and fillers) by two speech and language therapists. One-way ANOVAs showed that AWC use significantly more revisions than AWS and CTLs both when reading aloud and when describing pictures. AWC showed a trend toward increased co-articulation when describing a picture compared to AWS and CTL although this failed to meet significance level, AWC speaking rates was evaluated as similar to the two other groups. Results suggest that both spontaneous speech and oral reading outputs of AWC can be differentiated from AWS and CTL by the number of revisions used. We speculate that excessive co-articulation might differentiate AWC from AWS and CTLs in spontaneous speech but this does not appear to hold true for oral reading.